KARAKTERISTIK PENDERITA KEJANG DEMAM PADA BALITA RAWAT INAP DI RSUD Dr. PIRNGADI MEDAN TAHUN 2010-2011 - Syafni Rani; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Febrile convulsion is the commonest neurologis disorder in infant and child. Two to five percent of children in the world  have a febrile convulsion when ≤5 years old. More than 90% occur when <5 years old. The highest incidence occur when two years first life of children. To determine the characteristic of children ≤5 years old with febrile convulsion  were hospitalized in RSUD Dr. Pirngadi Medan in 2010-2011 with research descriptive case series design. Population and sample numbered 110  person (total sampling). Data obtained from medical records, analyze data using Chi-square, T-test and ANOVA. The results obtained that the children ≤ 5 years with febrile convulsion the highest proportion in age group 1-3 years are 57,3%; male 57,3% with sex ratio 1,3:1; normal weight birth 94,6%; good nutrition status 85,5%; febrile convulsion history  38,0%; fever of febrile convulsion with temperature >38⁰C - 39⁰C 40,9%; had tonsilopharynxitis 37,1%; simple febrile seizure 59,1%; medicine and lab 81,8%; the average threatment time was 4 days; own expense 59,1%; heal patients 50%; there was difference in the average treatment time based on the state of coming home (p=0,000). Suggested there are education for children under five’s mother in order can prevent her children from febrile convulsion when fever, and for mother who have children with febrile convulsion history in order can prevent febrile convulsion reccurence with way giving antipyretic and anticonvulsion to her children when start fever. Keywords: Febrile Convulsion, Characteristics of Patients, RSUD Dr. Pirngadi Medan